Simulation Learning in Economics Education: Empowering Critical Thinking and Rahmatan Lil Alamin Value - Farid, Imam (Tadibia Islamika: Journal of Holistic Islamic Education, 2023)
This study explores the application of critical education paradigms, particularly Rahmatan Lil Alamin, to enhance critical thinking skills in economics subjects through simulation learning methods. Critical education aims to challenge unjust social structures and systems by cultivating critical consciousness and empowering individuals. Simulation learning is employed as a means to promote active student engagement and stimulate critical thinking. Drawing upon literature reviews highlighting the effectiveness of simulation methods in improving critical thinking, the study investigates the impact of these methods on high school students' critical thinking skills. The literature underscores the importance of interaction, communication, and role-playing in the learning process, aligning with the goals of critical education. The research delves into understanding how simulation methods can enhance critical thinking skills in economics subjects and the effects of such methods on student learning. The study is conducted in a Madrasah Aliyah Negeri in Batang, Indonesia, where learner-centered education is practiced, providing an ideal setting for implementing simulation-based critical education. Data collection methods include observation, interviews with teachers and students, and documentation analysis. The research employs a qualitative case study approach to gather rich data and insights into the implementation of simulation methods in economics education. Preliminary findings indicate that the simulation method fosters active participation, stimulates critical thinking, and raises awareness of real-world societal issues. Students engage in respectful discussions, considering diverse viewpoints and demonstrating tolerance, aligning with the Rahmatan Lil Alamin concept.